Association between female reproductive factors and intraocular pressure according to glaucoma status: A cross-sectional study of the Korea National Health and Nutrition Examination Survey - Ji Eun Song; Mi Yeon Lee; Chungkwon Yoo; Joon Mo Kim (PLoS ONE, 2026)
Background To investigate the association between endogenous estrogen exposure and intraocular pressure (IOP) in postmenopausal women stratified by glaucoma status. Methods This population-based, cross-sectional study analyzed 1,823 postmenopausal women aged ≥50 years from the Korea National Health and Nutrition Examination Survey (2010–2011). Age at menarche, and menopause, reproductive span, and time since menopause were used as surrogate markers of lifetime estrogen exposure. Multivariate linear regression analyses were performed for the non-glaucoma and glaucoma groups, adjusting for confounders. Results Among women without glaucoma, indicators of longer estrogen exposure were significantly associated with higher IOP. Menopause at the age of ≥49 years and reproductive span of ≥33 years were associated with IOP increases of 0.79 mmHg and 0.88 mmHg, respectively. Conversely, in women with glaucoma, longer estimated estrogen exposure was associated with lower IOP. Menopause at ≥48 years of age and reproductive span at ≥31 years were not associated with IOP reduction. These findings demonstrate distinct associations between endogenous estrogen exposure proxies and IOP in women with and without glaucoma. Conclusions Our results suggest a context-dependent role of estrogen in ocular physiology, with potential implications for glaucoma risk assessment and the development of preventive strategies in aging women.